THE ASSESSMENT OF TREATMENT ADHERENCE AMONG DIALYSIS PATIENTS - ZAINAB , R; Arif, S; SADDIQUE, H; TASNEEM , SS (Biological and Clinical Sciences Research Journal, 2024)
Treatment adherence among dialysis patients is crucial for improving health outcomes and reducing complications associated with chronic kidney disease (CKD). However, adherence rates are often suboptimal due to complex treatment regimens and psychosocial factors. Objective: This study aims to assess treatment adherence among dialysis patients and identify factors influencing adherence behaviors. Methods: A descriptive cross-sectional study was conducted at Jinnah Hospital, Lahore, involving 133 patients with end-stage kidney disease (ESKD) undergoing dialysis. Data were collected using a validated questionnaire covering demographics and adherence behaviors across medication intake, dietary and fluid restrictions, and session attendance. Descriptive and inferential statistical analyses were performed using SPSS version 22, with a significance threshold set at p < 0.05. Results: Among the participants, 33.1% displayed poor adherence, 45.1% showed moderate adherence, and only 21.8% exhibited good adherence. Factors associated with non-adherence included forgetting medication (58.6%), intentional session shortening (43.6%), and inconsistent fluid restriction compliance (35.3%). Conclusion: The findings highlight moderate to poor adherence levels among dialysis patients, emphasizing the need for multifaceted interventions. Enhanced patient education, support systems, and multidisciplinary collaboration are recommended to improve adherence rates and health outcomes.